Odpowiedzi

2010-03-08T17:04:25+01:00
1. 3(2x-1)+4(y-2)=9
2(5x-1)+3y=5(3x+y)+2

6x-3+4y-8=9
10x-2+3y=15x+5y+2

6x+4y=20
10x-15x-5y+3y=2+2

6x+4y=20 /*5
-5x-2y=4 /*6

30x+20y=100
-30x-12y=24
+____________
8y=124 /:8
y=15,5

y=15,5
6x+4y=20

y=15,5
6x+4*15,5=20

y=15,5
6x+62=20

y=15,5
6x=-42 /:6

x=-7
y=15,5
| | | | | | |
2(x+y)-3(x-2y)=-7x-2
5(x+1)-2(3-y)=-4(x+y)

2x+2y-3x+6y=-7x-2
5x+5-6+2y=-4x-4y

-x+7x+8y=-2
5x+4x+2y+4y=-5+6

6x+8y=2 /*3
9x+6y=1 /*(-2)

18x+24y=6
-18x-12y=-2
+__________
12y=4 /:12
y=1/3

y=1/3
6x+8y=2

y=1/3
6x+8*1/3=2

y=1/3
6x+2 2/3 =2

y=1/3
6x=-2/3 /:6

x=1/9
y=1/3
| | | | | | | |
4(x+2)-3(y-1)=x+y-3
3(x-4)-2(y-2)=4(x-y)+4

4x+8-3y+3=x+y-3
3x-12-2y+4=4x-4y+4

3x-4y=-14
-x+2y=12 /*(-1)

3x-4y=-14
x=-12+2y

3(-12+2y)-4y=-14
x=-12+2y

-36+6y-4y=-14
x=-12+2y

2y=22 /:2
x=-12+2y

y=11
x=-12+22

x=10
y=11

Mam nadzieje, że pomogłam
Pozdrawiam!!!